IMPLEMENTATION OF INSTRUCTIONAL LEADERSHIP WITH TOTAL QUALITY MANAGEMENT: BRIDGE NODES IN EDUCATIONAL COMMUNICATION NETWORKS - Muhamad Latif Mahtum; Cepi Triatna; Cucun Hasanah (LP2M IAIN Sultan Amai Gorontalo, 2025)
The era of global educational transformation demands integration of instructional leadership with Total Quality Management (TQM). The research gap lies in the limited qualitative studies exploring critical bridge nodes as leverage points for organizational transformation. This study aims to explore the implementation of instructional leadership integrated with TQM through the identification of bridge nodes in Indonesian educational organizational communication networks. The research uses a qualitative approach with a single case study design in a senior high school. Data were collected through in-depth interviews with eight informants using purposive sampling. Analysis used ATLAS.ti with a qualitative network analysis approach to identify bridge nodes and communication network patterns. The research identified three main findings: universal consensus (100%) on the effectiveness of principal feedback; significant conceptual divergence (57.1%) in educational quality definitions reflecting organizational maturity; and three critical bridge nodes, namely open communication culture, constructive feedback, and holistic quality, as vital coordination mechanisms. TQM principles can be effectively applied in the Indonesian educational context through responsive adaptation to local cultural characteristics. The identified bridge nodes become strategic leverage points for sustainable organizational transformation.